2022
DOI: 10.3390/ijerph19159614
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Using a Low-Cost and Easily Accessible Exercise Toolkit Incorporated to the Governmental Health Program on Community-Dwelling Older Adults: A Quasi-Experimental Study

Abstract: The Community Care Station (CCS) service was initiated by the Taiwanese government as a part of its elderly social services programs. This study aimed to investigate the effects of using an inexpensive exercise toolkit, containing a stick, theraband, sandbag and a small ball, led by a physical therapist among community-dwelling older adults participating in CCS. A total of 90 participants (aged 77.0 ± 6.8 years) were recruited and divided into an intervention group (n = 45) and a comparison group (n = 45). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 40 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…On other occasions, exercise programs are structured to rely on high-cost resistance and cardiorespiratory machines (i.e., treadmills), which is not ecologically feasible, as funds are limited. Community exercise programs supervised by exercise physiologists for aged adults and older, using low-cost equipment like that used in their daily activities (e.g., dumbbells, which are similar to small packages) could be an opportunity to promote functional fitness [ 10 ]. Thus, the search for reliable long-term and low-cost exercise interventions is warranted for the purpose of increasing physical and functional fitness among those aged adults intending to be physically active [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On other occasions, exercise programs are structured to rely on high-cost resistance and cardiorespiratory machines (i.e., treadmills), which is not ecologically feasible, as funds are limited. Community exercise programs supervised by exercise physiologists for aged adults and older, using low-cost equipment like that used in their daily activities (e.g., dumbbells, which are similar to small packages) could be an opportunity to promote functional fitness [ 10 ]. Thus, the search for reliable long-term and low-cost exercise interventions is warranted for the purpose of increasing physical and functional fitness among those aged adults intending to be physically active [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be associated with the fact that authors may assume that other researchers are familiar with the general exercise protocols and only include essential details for the specific study. Additionally, various studies have tested exercise intervention exclusively in the elderly, excluding those that are transitioning to this age phase [ 9 , 10 ]. This gap should be tested as a means to provide the validity of the same exercise program for both older adults and those approaching this age group.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the included studies are presented in Table 1 . One study was conducted in Israel [ 67 ], four in Korea [ 60 , 62 , 70 , 78 ], four in Japan [ 31 , 61 , 66 , 69 ], and 20 in China [ 34 - 36 , 59 , 63 - 65 , 68 , 72 , 73 , 75 - 77 , 79 - 81 , 83 - 86 ]. There were 16 RCTs [ 34 - 36 , 62 , 67 - 70 , 74 , 76 - 81 , 86 ], and 13 quasi-experimental studies [ 31 , 59 - 61 , 63 - 66 , 72 , 73 , 75 , 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study was conducted in Israel [ 67 ], four in Korea [ 60 , 62 , 70 , 78 ], four in Japan [ 31 , 61 , 66 , 69 ], and 20 in China [ 34 - 36 , 59 , 63 - 65 , 68 , 72 , 73 , 75 - 77 , 79 - 81 , 83 - 86 ]. There were 16 RCTs [ 34 - 36 , 62 , 67 - 70 , 74 , 76 - 81 , 86 ], and 13 quasi-experimental studies [ 31 , 59 - 61 , 63 - 66 , 72 , 73 , 75 , 82 , 83 ]. The mean sample size of all included studies was n=198 and the mean age of all participants was 71.65±6.34 years.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed mean and median values of TUG and gait speed or used Pearson and Spearman correlations between the two measures [21][22][23]42]. Herman et al found normal distribution of TUG results in 265 healthy older adults.…”
Section: Discussionmentioning
confidence: 99%